BIM-based automated design and planning for boarding of light-frame residential buildings - Liu, Hexu; Singh, Gurjeet; Lu, Ming; Bouferguene, Ahmed; Al-Hussein, Mohamed (Automation in construction, 2018)
Building information modelling technology provides a game-changing solution to address the challenges encountered in the AEC industry. However, this technology currently is not sufficient to fulfil the needs of construction practitioners in terms of proactive design and planning for boarding of light-frame residential buildings. This is partially due to the fact that boarding design and planning requires trades' know-how and substantial manual effort in developing the building information models. Current manual and ad hoc decision making for boarding of light-frame buildings leads to the generation of a significant amount of material waste. This research thus proposes a rule-based automated building information model (BIM) approach for designing boarding layout and planning material sheet cutting, resulting in practically feasible solutions with minimal material waste. In this research, object-based computer-processable layout design rules are comprehensively formalised based on trades' know-how. On this basis, rule-based design algorithms are further developed and integrated with mathematical algorithms in order to automatically generate design and planning alternatives while minimising material waste. Rich information in the BIM is leveraged to automate the rule-based boarding design and planning. A prototype system is developed based on Autodesk Revit via Application Programming Interface. A typical wood-framed residential building is used as a case study to test the developed prototype system. The results show the proposed approach successfully preserves the know-how of senior trades people while also minimising material waste in automating the boarding design and planning. •Improper boarding design and planning leads to a significant amount of material waste.•A rule-based automated BIM approach to boarding design and planning is proposed.•Rule-based design algorithms are developed to automate the boarding design.•Design rules are comprehensively formalised based on trades' know-how.•A prototype system is developed as an Autodesk Revit add-on tool for demonstration.